Produção de couve chinesa em função da fertirrigação nitrogenada e potássica nas mudas - Cardoso, Antonio Ismael Inácio [UNESP]; Piedade, Maria Beatriz S.; Rodrigues, Júlia Maria [UNESP]; Ricardo, Luiz Eduardo [UNESP] (FapUNIFESP (SciELO), 2017)
Few researches are available about the influence of nitrogen and potassium application in brassica seedlings production; so, we aimed to evaluate the effect of rates of nitrogen and potassium, provided by fertigation to seedlings produced in coconut fiber substrate, on chinese cabbage production. Sixteen treatments were studied, resulted from the factorial four N rates (0, 80, 160 and 240 mg/L) x four K2O rates (0, 100, 200 and 300 mg/L), in the completely randomized block design, with four repetitions. Sowing of hybrid Kukai 65 was done in polypropylene trays with 200 cells, filled with coconut fiber, in January 13, 2014. Fertilization was done by fertigation at 7, 14 and 21 days after sowing (DAS), using 500 mL of solution in each application in each plot, consisting of 50 cells. After transplantation, all plants received the same cultural practices, including initial and top-dressing fertilization. There was a linear increasing for all aboveground part vegetative traits of seedlings (30 DAS) the higher de N rate was observed, and quadratic effect for roots dry matter. The increase of potassium rates resulted in decreasing linear effect for root dry weight of seedlings and increasing linear effect for height and fresh weight of aboveground part of seedlings. Quadratic effects were observed for number of leaves, height and dry weight of plants for N rates evaluated at harvesting (96 DAS), with maximum estimated in 47.7 leaves, 35.5 cm and 68 g, for rates of 101, 131 and 138 mg/L of N, respectively. For K rates, decreasing linear effect for plant height was observed and quadratic for number of leaves and fresh weight of plants, and the highest fresh weight of plants (1.56 kg) at harvesting was estimated for rate of 140 mg/L of K2O.
Chinese cabbage production in function of nitrogen and potassium fertigation of seedlings
Keywords: Brassica pekinensis; Coconut fiber; Fertilization; Nitrogen; Potassium; Sexual propagation